Molecular Dynamics Study of Peptide in Water at Different Temperature (Journal of Nepal Physical Society, 2023)
Molecular dynamics approach has been carried out to study the structural properties of peptide to estimate the self-diffusion coefficients of water at different temperatures 290 K, 300 K, and 310 K respectively. The energy profiles show the stability of system which ensures a well-balanced molecular structure of the system. The radial distribution functions (RDFs) of the solvent-solvent, solute-solute, and solute-solvent show the distribution of system within the required references. The self-diffusion coefficients of water have been determined using respective mean square displacement (MSD) curves through the Einstein’s relation. The self-diffusion coefficients of water at different temperatures are 0.44 ×10-5 cm2s-1, 0.48 ×10-5 cm2s-1, and 0.50 ×10-5 cm2s-1 respectively. Calculations show that the MSD of water throughout the system is increasing on increasing temperature. The results are also valid with the theoretical as well as available experimental data.